Surface Doping of Sn in Orthorhombic CH3NH3PbI3 for Potential Perovskite Solar Cells: First Principles Study - Pramchu S. (2017)
© 2016 Elsevier B.V. We employed the density functional theory (DFT) based on plane wave pseudopotential method to investigate the structural and optical properties of Sn-incorporated orthorhombic CH 3 NH 3 PbI 3 , especially surface doping. The results from formation energies and chemical potential diagrams indicate that the condition defined between Pb-rich and I-rich is the most suitable condition to incorporate Sn into CH 3 NH 3 PbI 3 structure because formation energy of the impurity structure is lower than that of the undoped surface structure. Consequently, Sn doping can also stabilize surface structure. We found that the substitution of Sn for Pb atom on CH 3 NH 3 PbI 3 surface significantly reduces E g by 0.24 eV, compared with that of bulk doping. Therefore, the impurity of Sn on CH 3 NH 3 PbI 3 surface displays better improvement of optical properties and allows the perovskite to absorb light in a wider range (near-IR region) of wavelength in solar radiation.